Meaning Coconstruction in Group Counseling: The Development of Innovative Moments. Issue 4 (2nd October 2017) - Esposito, Giovanna; Ribeiro, Antonio P.; Alves, Daniela; Gonçalves, Miguel M.; Freda, Maria Francesca
Abstract : This study discusses a model of group counseling, the narrative mediation path (NMP), which is a unique narrative, multimodal approach that combines four narrative modes (metaphoric, iconographic, writing, and bodily ) and the narrative group. The purpose of the NMP is to foster reflexive processes with underachieving university students and to improve their academic performance. The study analyzes a single case of group counseling for seven underachieving economics students at an Italian university and the process of meaning construction among NMP narrative modes and the follow-up session. It applies the innovative moments coding system, a reliable method for studying change by tracking narrative innovations in sessions. More specifically, we focus on how innovative moments (IMs: action, reflection, protest, and reconceptualization) evolve during the four different narrative modes and the follow-up session. The findings suggest that the NMP fosters narrative innovations, mainly of a reflexive nature (reflection and reconceptualization). Moreover, during counseling and the follow-up session, the pattern of change is primarily characterized by reconceptualization IMs, the most complex form of narrative innovation.